A generalized super AKNS hierarchy associated with orthosymplectic Lie superalgebra OSP(2, 2) and its super bi‐Hamiltonian structures. (20th January 2020) - Yu, Jing; Han, Jingwei; Li, Chuanzhong
Abstract : For the orthosymplectic Lie superalgebra O S P ( 2, 2 ), we choose a set of basis matrices. A linear combination of those basis matrices presents a spatial spectral matrix. The compatible condition of the spatial part and the corresponding temporal parts of the spectral problem leads to a generalized super AKNS (GSAKNS) hierarchy. By making use of the supertrace identity, the obtained GSAKNS hierarchy can be written as the super bi‐Hamiltonian structures.